Ivy and Bean take care of the babysitter - Barrows, Annie (Barrows, Annie. Ivy + Bean., 2008)
When Bean's parents leave her in the care of her older sister Nancy for the afternoon, she enlists her neighbor and best friend Ivy to come over and teach Nancy how to be a really good babysitter.